2024
DOI: 10.3389/fenvs.2024.1339928
|View full text |Cite
|
Sign up to set email alerts
|

The dilemma of land green use efficiency in resource-based cities: a perspective based on digital transformation

Qiulan Qian,
Shuangcheng Luo

Abstract: Introduction: Improving land use efficiency is a necessary way to promote sustainable urban development. The objective of this study is to examine the issue of land green use efficiency (LGUE) in resource-based cities and analyze the impact of digital transformation on LGUE. The research utilizes data from 113 resource-based cities in China spanning from 2008 to 2020.Methodology: Firstly, using the stochastic frontier analysis (SFA) to measure LGUE in China cities, this paper investigates the spatial and tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…This study analyzed the land use of different industrial types from the micro level and the focus on the rational land utilization [7]. However, an analysis from the micro perspective cannot effectively solve the external impact, so the attention of scholars to land studies has increasingly shifted to the macro level, thus tending toward provincial level [8], urban agglomeration, [9] and prefecture-level city studies [10], where the focus is on spatiotemporal features and influential factors [11,12]. Lin and Ling (2021) found that the ULUE in the Yangtze River Delta has steadily improved, and the spatial difference has gradually expanded [13].…”
Section: Introductionmentioning
confidence: 99%
“…This study analyzed the land use of different industrial types from the micro level and the focus on the rational land utilization [7]. However, an analysis from the micro perspective cannot effectively solve the external impact, so the attention of scholars to land studies has increasingly shifted to the macro level, thus tending toward provincial level [8], urban agglomeration, [9] and prefecture-level city studies [10], where the focus is on spatiotemporal features and influential factors [11,12]. Lin and Ling (2021) found that the ULUE in the Yangtze River Delta has steadily improved, and the spatial difference has gradually expanded [13].…”
Section: Introductionmentioning
confidence: 99%